Analisis Keterikatan Pemangku Kepentingan (Stakeholder Engagement) pada Banksasuci Foundation di Kabupaten Tangerang - Petri Sri Handayani; Udin Syamsudin; Eko Prasetyo (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
The purpose of this research is to determine stakeholder management by the Banksasuci Foundation to be able to maintain the sustainability of the organization and work programs, and classify them into 4 indicators using a matrix in accordance with the theory of Bryson and Patton (2015) which suggests that stakeholder grouping is based on interests ( interest) and influence (power), with indicator dimensions, namely: (1) Players; (2) Subject, (3) Costest; and (4) Crowd. This researcher uses a post positivism paradigm with a descriptive research type and a qualitative approach. The results of the interview show that the stakeholders in the Banksasuci Foundation are; Cisadane Ciliwung River Basin Center, Government/Environmental Service (DLH), Private Sector/Companies, and Academics. Through this stakeholder analysis, it is hoped that the Banksasuci Foundation can more easily optimize each stakeholder.